ANALISIS FAKTOR PENGHAMBAT EFEKTIVITAS PENGELOLAAN SAMPAH DI KABUPATEN MIMIKA - Ryandy Fermat Silolongan; Try Apriyono (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2019)
This study aims to determine constraining factors of the effectiveness of waste management in the city of Timika in terms of of storage, collection, transfer, transportation, and processing of the waste. This research used descriptive method to describe the constraining factors of the effectiveness of waste management.. Data collection occupied by observation and questionnaires. Data analysis used Rating Scale and Z Test. The results of the analysis showed that the value of -Ztable> - Zaccount. Therefore storage, collection, transfer, transportation, and waste processing werethe constraining factors of the effectiveness of waste management in Mimika Regency